Rheumatic Diseases and Molecular Physical Medicine – New Aspects - Lange, Uwe; Müller-Ladner, Ulf; Dischereit, Gabriel (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2017)
A multimodal treatment of rheumatic diseases without physical medicine is incomplete. However, the mechanisms underlying the beneficial effects of physical medicine are only partially understood. Modern molecular medicine offers new insights into pivotal mechanisms and mediators of the inflammatory process and into interactions between cells of the immune system and bone cells. Investigating the potential influences of different methods of physical medicine on the central regulatory processes of inflammatory rheumatic diseases is of great interest, highly fascinating and opens up new avenues of research for the future. This article focuses on the novel results of molecular physical medicine in rheumatic diseases and osteoporosis.
Keywords: musculoskeletal diseases; physical medicine; molecular physical medicine; osteoporosis; cytokines